THE INFLUENCE OF ENTREPRENEURSHIP KNOWLEDGE AND FAMILY ENVIRONMENT ON ENTREPRENEURIAL INTEREST OF 11TH GRADE STUDENTS AT SMK NEGERI 10 JAKARTA - Mulya, Rika Noviana; Purwana, Dedi; Usman, Osly (Transpublika Publisher, 2023)
This study aimed to examine the influence of Entrepreneurship Knowledge and Family Environment on Interest in Entrepreneurship among Class XI students at SMKN 10 Jakarta. The research utilized a survey method with a quantitative approach to collect data from a population of 246 students. A probability sampling technique with the Slovin formula was applied, resulting in a sample of 154 students. Data analysis was performed using validation and reliability tests with IBM SPSS software version 24. The study findings revealed significant results. Firstly, a positive and significant correlation was found between Entrepreneurship Knowledge and Interest in Entrepreneurship, indicating that higher levels of knowledge in entrepreneurship positively impact students' interest in entrepreneurial activities. Secondly, the Family Environment demonstrated a positive and significant influence on Interest in Entrepreneurship, suggesting that a supportive and encouraging family environment contributes to students' inclination towards entrepreneurship. Lastly, the combined effect of Entrepreneurship Knowledge and Family Environment showed a significant influence on Interest in Entrepreneurship, emphasizing the importance of both factors in fostering students' interest in entrepreneurial pursuits. These results provide valuable insights for educators and policymakers to design effective strategies that promote entrepreneurship among students. Encouraging the acquisition of entrepreneurship knowledge and fostering a supportive family environment may significantly enhance students' interest and readiness to engage in entrepreneurial ventures.